The case of the missing mushroom: a novel bioluminescent species discovered within Favolaschia in southwestern China - Nimalrathna, Thilina S.; Tibpromma, Saowaluck; Nakamura, Akihiro; Galappaththi, Mahesh C.a.; Xu, Jianchu; Mortimer, Peter E.; Karunarathna, Samantha C. (Phytotaxa, 2022)
Seven species of bioluminescent mushrooms belonging to seven genera have been described in the tropical rainforests of China. This study contributes the eighth species, found growing on decaying bamboo in Xishuangbanna Tropical Botanical Garden (XTBG). Morphological characteristics and phylogenetic analyses using internal transcribed spacer (ITS) and ribosomal large subunit (LSU) gene regions placed the species within the genus Favolaschia. Comprehensive morphological descriptions, micro and macro photographs, and a phylogenetic tree showing the placement of the new species are provided. This is the second report of bioluminescent Favolaschia in China.